2015
DOI: 10.1007/s12083-015-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of indoor localization based on an experimental study of RSSI using a wireless sensor network

Abstract: In this paper, we present the implementation of a new indoor localization system. We studied the behavior of the Received Signal Strength Indication (RSSI) for different configurations depending on the initial energy level of the sensors used. The choice of the best XBee configuration for each sensor is obtained after studying the standard deviation of the RSSI. Thus, we performed an indoor localization application using three algorithms based on the RSSI fingerprinting. Several experiments were conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although this method saves the time and labor of fingerprint location in measuring RSSIs in many locations, as well as facilitating deployment in WSNs, there is a big deviation between the model of RSSI and distance established by it and the relationship between RSSI and distance in the actual environment, especially in a multipath environment. Aside from LNSM, other models have been used to describe the relationship between RSSI and distance, such as the free space propagation model (FSPM) [34] and the two-ray ground reflection model (TGRM) [8]. FSPM establishes the relationship between RSSI and distance when a wireless signal propagates in open space, so it does not consider the reflection effect of the ground and obstacles on the signal.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method saves the time and labor of fingerprint location in measuring RSSIs in many locations, as well as facilitating deployment in WSNs, there is a big deviation between the model of RSSI and distance established by it and the relationship between RSSI and distance in the actual environment, especially in a multipath environment. Aside from LNSM, other models have been used to describe the relationship between RSSI and distance, such as the free space propagation model (FSPM) [34] and the two-ray ground reflection model (TGRM) [8]. FSPM establishes the relationship between RSSI and distance when a wireless signal propagates in open space, so it does not consider the reflection effect of the ground and obstacles on the signal.…”
Section: Related Workmentioning
confidence: 99%
“…The WSNs are a kind of self-organizing network composed of many nodes with wireless transceivers, microprocessors, and sensors [4][5][6]. The received signal strength indication (RSSI) is the easiest to measure by a wireless transceiver, so it is often used to estimate distances and locations between nodes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Sevtsuk et al [36] showed that WiFi counts can be collected and mapped to visually represent occupant spatial intensities which can be used by universities to identify space utilization rates. El Amine et al [37] and Mardini et al [38] proposed a more sophisticated and advanced WiFi-based occupant detection solution. These studies estimated occupants' location using ZigBee, and XBee networks and developed algorithms to estimate RSS Indication (RSSI) fingerprinting which detected occupants' locations within 0.8 m. On the other hand, the study by Martani et al [7] showed that only 40% of building occupants were connected to the WiFi network, raising concerns about this solution's reliability.…”
Section: Wireless Network-based Solutionsmentioning
confidence: 99%
“…Large-scale positioning experiments indicated that the algorithm is effective and accurate. Another novel algorithm using RSSI mapping N°3 20 has been proposed where the localization accuracy is improved by multi-powerful classifiers. Meanwhile, there were some state-of-the-art localization algorithms reported.…”
Section: Introductionmentioning
confidence: 99%